The end of the Ottoman Empire as reflected in the İstanbul bourse. Issue 3 (2nd July 2016) - Hanedar, Avni Önder; Hanedar, Elmas Yaldız; Torun, Erdost
ABSTRACT: The Ottoman Empire faced catastrophic events during its period of dissolution which started with the First World War. At the end of this war, the Ottoman lands were shared by the Allied forces. As a reaction to this occupation, the Turkish War of Independence started in 1919 and finished in 1923. The authors aim to examine how these events were reflected in the İstanbul bourse, using Ottoman government bond prices data between 1918 and 1925. Econometric methodology of Carla Inclan and George Tiao (1994 ) identifies several break points, which imply a lower risk for the repayment of the bonds during the end of the First World War and the Turkish War of Independence.